THE EFFECT OF INDIVIDUAL CHARACTERISTICS TO ORGANIZATIONAL PERFORMANCE AND EMPLOYEE SATISFACTION - Mutia Arda, SE, M.Si (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
The strategy of a company or organization is an area of study that is always interesting to be observed. Business organizations live in a competitive environment, for which the business organization continues to make efforts that can strengthen its existence by creating competitive advantage in its environment. This effort can be possible if the business organization has competent human resources. However, the problem that is often faced by business organizations is the lack of human resources that have sufficient competence to run the business strategy to be able to create competitive advantage. This is where the roles and responsibilities of human resource management to be able to overcome these problems. The purpose of this paper is to describe the business management strategy in order to create competitive advantage through the competencies seen from individual characteristics (age, experience, education, and gender) within an organization that affect job satisfaction of each employee and impact on organizational performance.